Gender, smart mobility and COVID-19 - Carboni, A.; Costa, M.; Kalakou, S.; Pirra, M. (HCI in Mobility, Transport, and Automotive Systems. Lecture Notes in Computer Science, 2021)
The COVID-19 pandemic has strongly impacted people’s main routine, which certainly includes their mobility habits. This paper aims to assess the pandemic’s mobility impacts and whether these may have increased the already existing inequality between men and women. In particular, the variation of mode choice in a pre-COVID and post-COVID scenario is investigated, focusing on the use of transport mode defined as Smart Mobility. The analysis is performed on data collected in thirteen European countries between July and September 2020 through a survey designed using an intersectional approach. Responses are analyzed to highlight correlations between different factors affecting mobility changes: some interest is reserved to the modes used according to the journey scope (work, errand, shopping). Overall, results reveal more people walking for their daily journeys, while a significant decrease in the use of public transport is observed. Although these changes affect women more, the main reason behind this is the need for more safety in terms of low risk of contagion, irrespective of gender. A specific focus on using modes commonly associated with a Smart Mobility offer (such as shared modes, public transport, walking, and biking) reveals differences originating when comparing men and women responses and various age ranges.